PROGRESIVE MUSCLE RELAXATION MENURUNKAN FREKUENSI NYERI PADA PENDERITA KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI POSA RSUD DR.SOETOMO SURABAYA - Endang Kasih; Mira Triharini; Tiyas Kusumaningrum (Universitas Airlangga, 2019)
Introduction: Breast cancer pain occurs because inflammation, pain because of the edge receptor Nerve damage due to the inflammation or sandwiched posted swelling. Progresive muscle relaxation (PMR) Frequency Against breast cancer Pain Patients with chemotherapy at POSA Dr. Soetomo hospital.Methods: One group pretest – posttest design was used in this study. The population were the breast cancer patients with chemotherapy in POSA Dr. Soetomo amounting 30 respondents. There were 28 respondents as sample, taken according inclusion criteria. Independent variable of this research was PMR. Dependent variable was frequency of breast cancer pain. Data was collected by using questionaire and observation sheets. Data was analyzed using paired t test with level of significant <0.05.Results: Results showed there was effect of progressive muscle relaxation (PMR) frequency against breast cancer pain (p=0.000). Further research could continues with using different methods related to this experiment